Examining neurodiversity and student resources in an engineering universal design learning context - Taylor, Christa L.; Jang, Shinae; Motaref, Sarira; Roy, Manish; Chrysochoou, Maria; Zaghi, Arash Esmaili (Frontiers in Education, 2025)
IntroductionEnhancing inclusion in engineering education is a growing priority, with increasing attention directed toward supporting neurodiversity. Universal Design for Learning (UDL) has been identified as a particularly promising framework for addressing the diverse needs of this population. In response, targeted programs have been developed to apply UDL principles and foster more inclusive learning environments for neurodiverse students in engineering.MethodsTo explore whether characteristics of two types of neurodiversity (i.e., ADHD and depression) predict changes in academic engagement, learning motivation, and self-efficacy in a UDL context, undergraduate students in eight UDL-based engineering courses (the INCLUDE program) completed self-report measures at the beginning and end of their course.ResultsResponses (N = 563) were analyzed using latent change score modeling, which revealed different outcomes for ADHD and depression characteristics. Higher levels of ADHD characteristics predicted a small decrease in self-efficacy from the beginning of the course to the end, whereas higher levels of depression characteristics predicted moderate to large increases in learning motivation, self-efficacy, and academic engagement.DiscussionThese findings suggest that UDL-based interventions may differentially benefit students depending on neurodivergent characteristics, pointing to a need for more tailored support within inclusive frameworks.